Role of the pre-A motif in nitric oxide scavenging by truncated hemoglobin HbN of Mycobacterium Tuberculosis - Lama, Amriti (2009)
Mycobacterium tuberculosis truncated hemoglobin, HbN, is endowed with a potent nitric-oxide dioxygenase activity and has been found to relieve nitrosative stress and enhance in vivo survival of a heterologous host, Salmonella enterica Typhimurium, within the macrophages. These findings implicate involvement of HbN in the defense of M. tuberculosis against nitrosative stress. The protein carries a tunnel system composed of a short and a long tunnel branch that has been proposed to facilitate diatomic ligand migration to the heme and an unusual Pre-A motif at the N terminus, which does not contribute significantly to the structural integrity of the protein, as it protrudes out of the compact globin fold. Strikingly, deletion of Pre-A region from the M. tuberculosis HbN drastically reduces its ability to scavenge nitric oxide (NO), whereas its insertion at the N terminus of Pre-A lacking HbN of Mycobacterium smegmatis improved its nitric-oxide dioxygenase activity. Titration of the oxygenated adduct of HbN and its mutants with NO indicated that the stoichiometric oxidation of protein is severalfold slower when the Pre-A region is deleted in HbN. Molecular dynamics simulations show that the excision of Pre-A motif results in distinct changes in the protein dynamics, which cause the gate of the tunnel long branch to be trapped into a closed conformation, thus impeding migration of diatomic ligands toward the heme active site. The present study, thus, unequivocally demonstrates vital function of Pre-A region in NO scavenging and unravels its unique role by which HbN might attain its efficient NO-detoxification ability.